The dynamic relationship between inequality and sustainable economic growth - Seo, Hwan Joo; Kim, Hansung; Lee, Young Soo (Sustainability (Switzerland), 2020)
This study empirically tests the effects of income inequality on growth for 43 countries from 1991 to 2014 based on a cumulative growth model. The results show that, first, the estimation results using a reduced equation reveal a positive correlation between the income inequalities of lagging countries and the respective growth gaps with the frontier country. This confirms that the increase in income inequality negatively affects growth. Secondly, a cumulative growth model using 3SLS estimation shows that income inequality has a negative effect only on investment. However, we fail to find correlations between technological innovation and income inequality and between human capital accumulation and income inequality. Considering that investment has a positive impact on productivity, we conclude that income inequality has a negative impact on investment and that the resulting sluggish investment has a negative impact on productivity, which in turn negatively influences growth. Third, contrary to Kaldor and Barro’s prediction, we find that income inequality in developing countries is negatively correlated with growth, particularly for investment. The effects of income inequality on investment are found to be similar in both developed and developing countries. We also find region-specific differences in the paths through which income inequality affects sustainable economic growth.
Keywords: Income inequality; Innovation and human capital; Investment; Sustainable economic growth